An epidemiological study of burglary offenders: trends and predictors of self-reported arrests for burglary in theUnited States, 2002-2013 - DeLisi, Matt (International journal of offender therapy and comparative criminology, 2018)
Burglary is serious property crime with a relatively high incidence and has been shown to be variously associated with other forms of criminal behavior. Unfortunately, an epidemiological understanding of burglary and its correlates is largely missing from the literature. Using public-use data collected between 2002 and 2013 as part of the National Survey on Drug Use and Health (NSDUH), the current study compared those who self-reported burglary arrest in the prior 12 months with and without criminal history. The unadjusted prevalence estimates of self-reported burglary arrest were statistically different for those with a prior arrest history (4.7%) compared with those without an arrest history (0.02%) which is a 235-fold difference. Those with an arrest history were more likely to report lower educational attainment, to have lower income, to have moved more than 3 times in the past 5 years, and to use alcohol, tobacco, illicit drugs, and engage in binge drinking. Moreover, those with prior arrest histories were younger and more likely to be male. There is considerable heterogeneity among burglars with criminal history indicating substantially greater behavioral risk.